2022
DOI: 10.1002/ijgo.14135
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 vaccine on sperm quality

Abstract: Objective To examine the effect of the BNT162b, mRNA, SARS‐CoV‐2 virus vaccine on sperm quality. Methods This was a prospective cohort study conducted on sperm donors at the sperm bank of a tertiary, university affiliated medical center. All sperm donors donated sperm repeatedly and the average sperm parameters of all available samples were compared before and after receiving the SARS‐CoV‐2 vaccine. Each donor served as his own control. For all participants, at‐least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 17 publications
(26 reference statements)
2
58
0
1
Order By: Relevance
“…There were no significant effects on the other parameters such as semen volume, pH or sperm concentration morphology. Our data are in agreement with previous reports that reported no significant deleterious effects of mRNA COVID-19 vaccines on semen parameters [12][13][14]16]. Barda et al [16] found that total sperm count and total motile count increased after the second vaccine compared to samples before vaccination in a cohort of 33 healthy donors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were no significant effects on the other parameters such as semen volume, pH or sperm concentration morphology. Our data are in agreement with previous reports that reported no significant deleterious effects of mRNA COVID-19 vaccines on semen parameters [12][13][14]16]. Barda et al [16] found that total sperm count and total motile count increased after the second vaccine compared to samples before vaccination in a cohort of 33 healthy donors.…”
Section: Discussionsupporting
confidence: 93%
“…Barda et al [16] found that total sperm count and total motile count increased after the second vaccine compared to samples before vaccination in a cohort of 33 healthy donors. Sperm motility did not change after the vaccine [16]. In Lifshitz et al [14] study, none of the vaccinated men produced abnormal results apart from two participants (2 out of 75), one oligozoospermic, and one with reduced motility.…”
Section: Discussionmentioning
confidence: 83%
“…After the screening process, 39 articles were considered pertinent for potential inclusion and the full texts were retrieved. Finally, 29 articles [1] , [2] , [3] , [4] , [6] , [7] , [8] , [10] , [15] , [17] , [18] , [20] ; Gonzalez et al, 2021; Huang et al, 2022; Jacobs et al, 2022; Lifshitz et al, 2022; Mohr-Sasson et al, 2022; Morris, 2021; Morris et al, 2021; Odeh‐Natour et al, 2022; Orvieto et al, 2021; Reschini et al, 2022; Rozhivanov & Mokrysheva, 2021; Safrai, Herzberg, et al, 2022; Safrai, Kremer, et al, 2022; Soysal & Yılmaz, 2022; Wesselink et al, 2022; Xia et al, 2022; Zhu et al, 2022)were included in the systematic review and 20 articles [2] , [3] , [4] , [6] , [7] , [18] , [20] ; Gonzalez et al, 2021; Huang et al, 2022; Jacobs et al, 2022; Morris, 2021; Odeh‐Natour et al, 2022; Orvieto et al, 2021; Reschini et al, 2022; Rozhivanov & Mokrysheva, 2021; Safrai, Herzberg, et al, 2022; Safrai, Kremer, et al, 2022; Soysal & Yılmaz, 2022; Xia et al, 2022; Zhu et al, 2022) in the meta-analysis ( Figure 1 ).
Figure 1 Flowchart of the screening and selection process
…”
Section: Resultsmentioning
confidence: 99%
“… 14 Previous reassuring publications were mainly based on single pre‐ and single‐post‐vaccination samples per participant. 16 , 17 , 24 , 25 Safrai et al. investigated pre and post‐vaccination semen samples of 72 patients undergoing IVF treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few studies regarding the impact of COVID‐19 vaccine of semen parameters, resulting with overall reassuring results, some even reported parameters improvements post‐vaccination. 15 , 16 , 17 However, careful examination raises two questions. First, is there a biological rationale for semen parameters improvement post‐vaccination?…”
Section: Introductionmentioning
confidence: 99%